Birth Preparedness and Complication Readiness among Slum Women in Indore City, India (Journal of Health, Population and Nutrition, 2010)
Three hundred twelve mothers of infants aged 2-4 months in 11 slums of Indore, India, were interviewed to assess birth preparedness and complication readiness (BPACR) among them. The mothers were asked whether they followed the desired four steps while pregnant: identified a trained birth attendant, identified a health facility, arranged for transport, and saved money for emergency. Taking at least three steps was considered being well-prepared. Taking two or less steps was considered being less-prepared. One hundred forty-nine mothers (47.8%) were well-prepared. Factors associated with well-preparedness were assessed using adjusted multivariate models. Factors associated with well-preparedness were maternal literacy [odds ratio (OR)=1.9, (95%) confidence interval (CI) 1.1-3.4] and availing of antenatal services (OR=1.7, CI 1.05- 2.8). Deliveries in the slum-home were high (56.4%). Among these, skilled attendance was low (7.4%); 77.3% of them were assisted by traditional birth attendants. Skilled attendance during delivery was three times higher in well-prepared mothers compared to less-prepared mothers (OR: 3.0, CI 1.6-5.4) Antenatal outreach sessions can be used for promoting BPACR. It will be important to increase the competency of slum-based traditional birth attendants, along with promoting institutional deliveries. Key words: Birth preparedness; Complication readiness; Cross-sectional studies; Deliveries; Slums; Urban poor; India DOI: 10.3329/jhpn.v28i4.6045 J HEALTH POPUL NUTR 2010 Aug;28(4):383-391